The influence of present health status (post Covid-19) on retirement planning in Malaysia - Mohd Yaziz bin Mohd Isa; Mellisa Daukin (Global Business & Finance Review (GBFR), 2022)
Purpose: To investigate whether present health status influence retirement planning in the new economic challenge post Covid 19. The relationship between present health status and retirement planning should be better explored and investigated for strengthening the retirement planning among Malaysian women. Design/methodology/approach: This study is developed based on a quantitative approach where primary data was acquired through online surveys to 433 workers in various locations in Malaysia. The target population of this study are people who work full time in Malaysia's government and private sectors whose ages range from 25 to 55 years old. Findings: The significant result from this study has shown that there is a health status effect on the employees' retirement planning. The result identified that the health status is an important factor for retirement planning during the post-COVID-19 among the working population in Malaysia. Research limitations/implications: Even though the COVID-19 pandemic has caused many monetary, economic and social challenges, it has also opened up a new door opportunity for constructive change. Government, policymakers and the general public need more transparent and resourceful in making difficult choices and trade-offs between short-term and long-term concerns. Nevertheless, the real challenges exposed in the COVID-19 pandemic are the lack of progressive long-term thinking on retirement planning. This paper has its limitations, that since COVID-19 is still ongoing, this study only focuses on the current present health status of Malaysian employees. Originality/value: Studying the employee's behaviour during the times of distress is important to understand how do they manage their finances. This is a valuable knowledge that could be applied in future. Many employees were caught unaware and faced challenges in the recent past. This could be avoided if prior knowledge and the savings are available.
Keywords: 650; Covid-19; Latent Variable; Partial Least Square; Present Health Status; Retirement Planning; RMSEA